Respuesta :

Answer:

13+7√3

Step-by-step explanation:

The denominator will be rational when it is multiplied by the opposite ± expression, called the conjugate.

[tex]\frac{5 + \sqrt{3}}{2-\sqrt{3}}[/tex]

[tex]= \frac{5 + \sqrt{3}} {2-\sqrt{3}} X \frac{2+\sqrt{3}}{2+\sqrt{3}}[/tex]  Multiplying by 1 does not change the number. (It equals 1 because the numerator and denominator are the same).

[tex]= \frac{(5 + \sqrt{3})(2+\sqrt{3})} {(2-\sqrt{3})(2+\sqrt{3})}}[/tex]

[tex]= \frac{10 + 5\sqrt{3} + 2\sqrt{3}+3 }{4 - 2\sqrt{3}+ 2\sqrt{3}-3}[/tex]  Distribute over brackets

[tex]= \frac{13 + 7\sqrt{3} }{4 -3}[/tex]  Combine like terms

[tex]= \frac{13 + 7\sqrt{3} }{1}[/tex]    

[tex]= 13 + 7\sqrt{3}[/tex]

ACCESS MORE